Nne (Things We Lost in the Fire, 2020)
BACKGROUND: Clinical reasoning is frequently underdeveloped in graduate nurse practitioner (NP) education. The National Organization of Nurse Practitioner Faculties Role Competencies define what NP students must achieve, and the Professional-Reporter-Interpreter-Manager-Educator-Nurse Practitioner (PRIME-NP) Model describes the sequence in which they develop. PROBLEM: Advanced Health Assessment students can perform a thorough physical examination but struggle to determine relevant findings, prioritize working differentials, and translate assessment data into provider-level clinical decisions. Faculty have the competencies students must reach, but not the classroom activities that build them. APPROACH: The Detective NP Pathway is a 6-level, interactive teaching method that supplies those activities. Each level pairs a reasoning task with a gamified virtual activity, a delivery platform, and the National Organization of Nurse Practitioner Faculties competency it develops. Students earn a digital badge at each level, giving faculty a competency-specific record of progress before clinical placement. CONCLUSIONS: This article describes the pathway and provides a faculty implementation guide.